Doing field projects methods and practice for social and anthropological research - Forrest, John 1951-; Nelson, Katie (John Wiley & Sons, 2022)
"Ethnographic fieldwork is the hallmark research approach of sociocultural anthropology. Its centrality has not waned since its inception more than a century ago, yet the variety of questions that fieldwork answers have expanded greatly. For instance, anthropologist Olga Lidia Olivia Hernandez studies Aztec dance collectives in multiple sites in Baja California, Mexico, and California, USA. She conducts fieldwork to understand why Aztec dance emerged as a form of ethnicity on the US - Mexico border among non-indigenous participants, and how national, political, religious, and bodily processes are involved in the reappropriation of Aztec dancing (Hernandez, 2018). Taking a more multidisciplinary approach in her fieldwork among Orangutan care workers in Borneo, anthropologist Juno Salazar Parreñas draws on anthropology, primatology, Southeast Asian history, gender studies, queer theory, and science and technology studies. She explores the violence care workers and Orangutans experience. She asks if conservation biology can turn away from violent techniques to ensure Orangutan population growth and embrace a feminist sense of welfare (Parreñas 2018). Anthony Kwame Harrison conducts fieldwork in San Francisco among the underground hip hop scene. Harrison interviewed area hip hop artists and also performed as the emcee "Mad Squirrel." His immersion in the subculture allowed him a unique vantage point to examine the changing nature of race among young Americans, as well as issues of ethnic and racial identification, and how different ethnic groups engage hip hop in different ways as a means to claim racial and establish subcultural authenticity. (Harrison, 2009)"--Provided by publisher.